Implementasi Raspberry Pi untuk membantu Klinik dan Pengembangan Website Klinik menggunakan Rapid Application Development - Mochammad Haldi Widianto; Della Ihsanti Kusnadi (Politeknik Negeri Cilacap, 2022)
The development of Internet of Things (IoT) tools and components has often been used in agriculture, plantations, and smart homes. One of the microcontroller components can take advantage of the Raspberry Pi because it is similar to a small computer. Another thing that makes web-based application development can take advantage of Rapid Application Development (RAD) because it is considered very flexible and can iterate on the design and development section where that section requires special focus due to the possibility of the same error. There are several studies related to utilizing website development to help in hospitals. However, the real problem is that technology such as clinical information websites has not been widely used for small clinics. This development website is supported by the location of the clinics, which are far from the urban center. The Others is supported by research on website development in clinics, not too many. So this study has a goal, namely the development of a website application with the help of a Raspberry Pi as a computer replacement medium (having wifi and a processor) which is applied to clinical LED TV because there is no computer to display it, and making the administration of the website itself tested by testing and evaluation using Black Box and User Acceptance Test (UAT). In testing and evaluation, it was found that 5 trials of Black Box testing got good results with all categories achieved. 71.06% of UAT results are included in the